ELAZIĞ İLİNDE GENÇLERDE ŞİDDETE BAŞVURMA YA DA MARUZ KALMA SIKLIĞI, ETKİLEYEN FAKTÖRLER VE ÖFKE İLE İLİŞKİSİ - AYGEN, MURAT (Fırat Üniveristesi, 2009)
Tüm toplumlarda gençler arasında şiddete başvurma ve maruz kalma son dönemlerde sık görülen önemli bir sorundur. Elazığ ilinde gençlerde şiddete başvurma ya da maruz kalma sıklığı, etkileyen faktörler ve öfke ile ilişkisini saptamak amacıyla yapılmıştır.Araştırmanın yapıldığı dönemde Elazığ il merkezinde bulunan toplam 35 lisenin tümü araştırmanın kapsamına alınmıştır. Bu liselerde okuyan toplam 22 480 öğrenci içerisinden n= Nt2pq / d2(N-1) + t2pq formülü kullanılarak 1463 kişi seçilmiş, tekrarlayan ziyaretlerle 1451'ine ulaşılmış, cevaplılık oranı %99.2 olmuştur. Çalışmada; şiddete maruz kalma ve baş vurma sıklığını ölçen soruların yanı sıra Spielberger tarafından geliştirilen Durumluk Sürekli Öfke İfadesi Envanteri kullanılmıştır.Çalışmaya alınan öğrencilerin yaş ortalaması 15.33 olup, %49.3'ü erkektir. %6.5'i gelir getirici bir işte çalışmaktadır. %10.3'ü sigara, %6.5'i alkollü içki, %4.9'u bağımlılık yapıcı madde kullandığını, %8.5'i şans oyunu/kumar oynadığını, %9.0'ı delici-kesici alet taşıdığını, % 5.1'i arkadaş grubu/çeteye üye olduğunu ifade etmiştir. %24.5'i arabesk müzik dinlemektedir. %33.2'si Elazığ'a göçle gelmiştir. Öğrencilerin %10.2'sinin babası, %38.1'inin annesi herhangi bir okul mezunu değildir. %18.8'inin babası annesini dövmektedir. Annesi babası tarafından dövülen çocukların %38.5'i bu olayı normal karşıladığını, her ailede olabileceğini ve kendisini fazla ilgilendirmediğini belirtmiştir. Öğrencilerin %20.5'i ebeveynlerinin kendisini halen dövdüğünü ifade etmiştir. Çalışmaya alınan öğrencilerin %12.2'si fiziksel, %20.7'si duygusal, %3.2'si cinsel şiddete halen maruz kaldıklarını belirtmişlerdir. Fiziksel şiddete erkek öğrenciler (%14.6), cinsel şiddete ise kız öğrenciler (%4.7) daha fazla maruz kalmaktadır (p<0.05). Öğrencilerin %31.7'si fiziksel şiddet, %41.5'i duygusal şiddet % 20.6'sı cinsel şiddet uyguladıklarını ifade etmiştir. Fiziksel ve cinsel şiddetti erkek öğrenciler kız öğrencilere göre daha fazla uygulamaktadırlar (p<0.05). Alkol ve bağımlılık yapıcı madde kullananların sürekli öfke, öfke iç ve öfke dış puanları kullanamayanlara göre yüksek saptanmıştır (p<0.05). Çeteye üye olanlar ile kavgada alet kullananların öfke iç, öfke dış (p<0.05), kumar oynayanların ise tüm öfke kompanentleri (sürekli öfke,öfke iç, öfke dış ve öfke kontrol) yüksek (p<0.05) saptanmıştır. Halen fiziksel şiddete maruz kalanların sürekli öfke, öfke iç, öfke dış puanları maruz kalmayanlara göre yüksek iken (p<0.05), sözel ve cinsel şiddete maruz kalanlar açısından anlamlı bir ilişki saptanmamıştır (p>0.05). Son bir yılda fiziksel şiddet ve duygusal/sözel şiddet uygulayanların ise sürekli öfke, öfke iç, öfke dış puanları yüksek saptanmıştır. Okula devamsızlık yapanların sürekli öfke, öfke iç ve öfke dış puanları yüksek bulunmuştur.Sonuç olarak; Elazığ ilindeki liselere devam eden öğrencilerin şiddete maruz kalma ve başvurma oranları oldukça yüksektir. Şiddete baş vurma ile öfke puanları arasında pozitif ilişki söz konusudur. Bu nedenle gençler arasında artan şiddete maruz kalma ve başvurma oranlarının düşmesini sağlayacak olan yasal düzenlemelerle birlikte eğitim ve hizmet sunumuna öncelik verilmelidir.

Recently, stronging arm and being exposed to violence among the young is a significant issue happening frequently in all societies. This study has been carried out for determining the frequency of stronging the arm or being exposed to it among the young in Elazıg City , the factors affecting it and its relation with the anger.Totally 35 high schools found at the city center during the period the research done have been included in the study. By using n= Nt2pq / d2(N-1) + t2pq formula, 1463 subjects have been selected from 22 480 students attending to these high schools, and 1451 of them have been contacted during the repeated visits, and the response correlation has been 99.2 % . In the study, State-Trait Anger Scale (STAS) developed by Spielberger has been used in addition to the questions measuring the frequency of stronging arm and being exposed to it.The age-average of the subjects in the study was 15.33, and 49.3 % of them were male. 6.5 % of them have been working in a wage-earning employment. 10.3 % of them have confessed that they have been smoking, 6.5 % drinking alcohol, 4.9 % taking drugs, 8.5 % playing game of chance or gambling, 9.0 % carrying stab, and 5.1 % being the members of the a friend-group or of a gang. 24.5 % have been listening to arabesque-music. 33.2 % have immigrated to Elazıg. The fathers of the 10.2 % and the mothers of the 38.1 % are not the graduates of any school. The fathers of the 18.8 % have been beating their mothers. 38.5 % of the children whose mothers are beaten by their fathers have expressed that they take it normally , it can happen in all families, and it does not interest themselves much. 20.5 % of the subjects have implied that their parents still have been beating themselves. Of the subjects included in the study ; 12.2 % have implied that they still have been exposed to physical, 20.7 % to sensual, and 3.2 % to sexual violence. Male subjects (14.6 % ) are exposed to the physical violence, and females (4.7 % ) to the sexual violence (p<0.05). 31.7 % of the subjects have expressed that they have commited physical violence, 41.5 % sensual violence, and 20.6 % sexual violence. The physical and sexual violence is commited more by the males than by the females (p<0.05). It has been seen that the permanent-anger, inner-anger and outer-anger points of the ones taking alcohol or drugs have been higher than the ones not taking (p<0.05). It has also been discovered that the inner-anger and outer-anger components of the members of the gang and of the ones using stab during the fight have been (p<0.05), and all components (permanent-anger, inner-anger ,outer-anger , and anger-control ) of the ones gambling have been high (p<0.05).While the permanent-anger, inner-anger ,outer-anger points of the ones being exposed to the physical violence have been higher (p<0.05) than the ones not exposed, it has not been determined a significant correlation with respect to the ones being exposed to the verbal and sexual violence (p<0.05). Within the last one year, it has been seen that the permanent-anger, inner-anger ,outer-anger points of the ones committing physical and sensual/verbal violence have been high. The permanent-anger, inner-anger according to the ones not committing violence,outer-anger points of the ones not attending to the school permanently have been high.Consequently, the correlation of committing and being exposed to violence among the high school students in Elazıg is too high. A positive correlation is in question between the anger-points and committing the violence . Therefore, education and service provider should attach priority together with the legal regulations to mintain the reduction of the ratios of committing and being exposed to violence icreasing among the young .
Relation amongst action of violence or suffering from violence in young population in elazig and affecting factors and anger
Keywords: Halk Sağlığı